PRIORITAS PENANGANAN JALAN KABUPATEN PIDIE MENGGUNAKAN METODE ANALISIS MULTI KRITERIA (AMK) - Thantawi Thantawi; Muhammad Isya; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
Pidie District has a district road length of 1,015 Km and is divided into 445 roads. The lack of funds makes it difficult to determine the priority of handling the road, it is necessary to examine the method of setting road priority in accordance with the needs of the community. The purpose of this study was to obtain criteria weights based on perceptions of importance between criteria using 15 stakeholder respondents and to determine the priority order of handling road infrastructure in Pidie District due to limited funding capacity in Pidie District Government using the Multi Criteria Analysis (AMK) method accessibility, regional development, economic sector development, cost aspects, environmental impact and road damage as the selection criteria. The results of this study are that road damage criteria get the highest weight, which is 0.197, then environmental impact criteria 0.190, economic development criteria 0.184, accessibility criteria for accessibility 0.152, regional development criteria 0.147 and cost aspect criteria 0.130. This can be interpreted that the aspect of road damage is a major consideration in determining the priority of road development in Pidie District but not significant to other criteria. Based on the weighting and scoring of these criteria, a sequence of priorities for road handling in Pidie District is obtained, where Jalan Bangkeh - Leupu is the first priority with a performance value of 4.152